Charter school report card - Tell, Shawgi (Critical constructions., 2016)
What is a charter school? Where do they come from? Who promotes them, and why? What are they supposed to do? Are they the silver bullet to the ills plaguing the American public education system? This book provides a comprehensive and accessible overview and analysis of charter schools and their many dimensions. It shows that charter schools as a whole lower the quality of education through the privatization and marketization of education. The final chapter provides readers with a way toward rethinking and remaking education in a way that is consistent with modern requirements. Society and its members need a fully funded high quality public education system open to all and controlled by a public authority.